KELEBIHAN & KEKURANGAN RAGAM UMPAN PANCING IKAN ARTIFISIAL BENTUK KATAK - Ardo Bernando (Universitas Mercu Buana, 2021)
Artificial fishing lures are of various shapes made to mimic animals that have become the natural diet of fish, one example is the frog-shaped which is generally used to lure predatory fish in freshwater waters. Over time, the various forms of frog bait are now increasingly diverse, so it is necessary to make an observation regarding each of its advantages and disadvantages by taking several representative product samples to be discussed in depth, provided that the criteria that the selected artificial bait product must still display characteristics the shape of a frog, so it's not just the name on the product packaging. The findings state that there are 7 types of frog-shaped bait, each of which is categorized according to its characteristic shape and movement which has advantages and disadvantages.